2019
DOI: 10.1002/jcp.28070
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from SDF1‐overexpressing mesenchymal stem cells inhibit ischemic myocardial cell apoptosis and promote cardiac endothelial microvascular regeneration in mice with myocardial infarction

Abstract: Exosomes extracted from mesenchymal stem cells (MSCs) was reported to reduce myocardial ischemia/reperfusion damage. Besides, stromal‐derived factor 1 (SDF1a) functions as cardiac repair after myocardial infarction (MI). Therefore, the present study aims to identify whether exosomes (Exo) released from SDF1‐overexpressing MSCs display a beneficial effect on ischemic myocardial infarction. Initially, a gain‐of‐function study was performed to investigate the function of SDF1 in ischemic myocardial cells and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…Currently, several strategies are under exploration that aim to enhance the exosomes released from MSCs. Hypoxia can facilitate MSCs to release exosomes, thus improving repair of cardiac tissues in a mouse model of myocardial infarction [274]. Compared with MSCs, exosomes derived from SDF1-overexpressing MSCs show enhanced therapeutic effects in myocardial infarction by increasing cardiac endothelial microvascular regeneration and inhibiting cardiomyocyte apoptosis in mice [275].…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%
“…Currently, several strategies are under exploration that aim to enhance the exosomes released from MSCs. Hypoxia can facilitate MSCs to release exosomes, thus improving repair of cardiac tissues in a mouse model of myocardial infarction [274]. Compared with MSCs, exosomes derived from SDF1-overexpressing MSCs show enhanced therapeutic effects in myocardial infarction by increasing cardiac endothelial microvascular regeneration and inhibiting cardiomyocyte apoptosis in mice [275].…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%
“…Human UC-MSC-EVs overexpressing the pro-survival Akt kinase was shown to modulate local angiogenesis in a preclinical rat model of MI, via PDGF-D as pro-angiogenic mediator [199]. Likewise, EVs from UC-MSCs overexpressing the tissue matrix metalloproteinase inhibitor 2 (TIMP2) or the cardioprotective stromal-derived factor 1 alpha (SFD1a) have been shown to limit detrimental ventricular remodelling via the pro-survival Akt/Sfrp2 pathway and to inhibit apoptosis and autophagy of myocardial cells while sustaining local angiogenesis in preclinical rodent models of MI [200,201]. MSCs derived from human term placenta, also referred to as amniotic mesenchymal stromal cells (AMSCs), are well-known for their (immuno)modulatory properties [202,203]; EVs released by human term placenta-MSCs have been recently demonstrated exertion of relevant therapeutic effects as supporting new vessel development in vitro and in vivo [204], with nitric oxide (NO)-releasing polymer stimulation as a functional trigger of exosomal enrichment of pro-angiogenic VEGF and miR-126 [205].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Recent studies have shown that MSC-based treatment of ischemia-induced cardiac damage can be mediated through the secretion of exosomes [5][6][7][8][9]. MSC-secreted exosomes have been reported to exert an anti-apoptotic effect on CMCs both in vivo and in vitro [5][6][7]10]. Exosomes exert their therapeutic effect by transferring lipids, proteins, and a variety of RNAs to recipient cardiac cells.…”
Section: Introductionmentioning
confidence: 99%